2022
DOI: 10.53967/cje-rce.v45i3.5219
|View full text |Cite
|
Sign up to set email alerts
|

La motivation scolaire d’élèves québécois du deuxième cycle du secondaire en temps de pandémie

Abstract: Pour comprendre comment le contexte d’enseignement à distance découlant de la COVID-19 est associé à la motivation scolaire des adolescents, nous avons mené une enquête auprès d’élèves de 3e, 4e et 5e année du secondaire (14 à 17 ans) en utilisant deux cohortes indépendantes : l’une de 601 élèves, recrutés en juin 2020 et ayant reçu un enseignement en ligne ; et l’autre de 3335 élèves, recrutés en février 2021 et ayant suivi un enseignement en ligne une journée sur deux pour la majorité de l’année scolaire. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Consequently, teachers during the pandemic were not necessarily in the mindset to prioritize the establishment of positive relationships with students. In line with this hypothesis, Falardeau et al (2022) have shown that school belonging was lower for a cohort of students that were taught during the pandemic years compared to a cohort of students taught before the pandemic.…”
Section: Caring Relationships With Teachersmentioning
confidence: 62%
“…Consequently, teachers during the pandemic were not necessarily in the mindset to prioritize the establishment of positive relationships with students. In line with this hypothesis, Falardeau et al (2022) have shown that school belonging was lower for a cohort of students that were taught during the pandemic years compared to a cohort of students taught before the pandemic.…”
Section: Caring Relationships With Teachersmentioning
confidence: 62%
“…Results from previous person-centred research (Litalien et al, 2019;Tóth-Király et al, 2022) suggest that a relatively small (3 to 5) number of motivation profiles should be identified (Hypothesis 1). Based on the negative impact of the pandemic on students' motivation and psychological need satisfaction reported in some previous studies (Falardeau et al, 2022;Janke et al, 2022;Usher et al, 2022), we also postulated that membership into profiles characterized by high levels of self-determined motivation would be less stable over time than membership into less desirable motivation profiles (Hypothesis 2). Second, this study aimed to investigate the role of the need-nurturing characteristics of the program educational climate and students' trait self-control in the prediction of profile membership, while controlling for sex and age.…”
Section: The Present Studymentioning
confidence: 97%
“…Indeed, prolonged campus closures imposed external restrictions on students who were forced to take all their courses online, thus interfering with the fulfilment of their need for autonomy ( Janke et al, 2022). Likewise, the sudden switch to distance learning disrupted learning processes, as many instructors were not prepared to move their classes online (Carrillo & Flores, 2020), just like many students did not have access to an optimal home setting for distance learning (Falardeau et al, 2022). This suboptimal learning environment is thus likely to have interfered with the fulfilment of students' need for competence.…”
Section: Predictors Of Academic Motivationmentioning
confidence: 99%